Epidemiology and Patient Distribution of Oral Cavity and Oropharyngeal SCC in Canada. Issue 4 (July 2020) - Ghazawi, Feras M.; Lu, Jessica; Savin, Evgeny; Zubarev, Andrei; Chauvin, Peter; Sasseville, Denis; Zeitouni, Anthony; Litvinov, Ivan V.
Background: Oral cavity cancers (OCCs) and oropharyngeal cancers (OPCs) continue to be a major source of morbidity and mortality worldwide requiring the shared effort of numerous specialists. Tobacco and alcohol consumption have long been identified as risk factors for both OCC and OPC. In addition, human papilloma virus (HPV) is gaining its position as the main causal agent for OPC. Objective: The objective of this study is to analyze the epidemiology of OCC and OPC in Canada. Methods: Data pertaining to the year of diagnosis, the patient's sex, age at the time of diagnosis, province/territory, city and postal code of oral cavity, and oropharyngeal malignancies diagnosed during 1992-2010 were extracted from the Canadian Cancer Registry and Le Registre Québécois du Cancer. Results: In total, 21 685 OCC cases and 15 965 OPC cases were identified from 1992 to 2010. Of those, 84.97% were oral cavity squamous cell carcinomas (SCCs), 88.10% were oropharyngeal SCCs, and both had a significant male predominance. While oral cavity SCC incidence stabilized over the study period, oropharyngeal SCC continued to increase. Oral cavity SCC incidence increased with age, while oropharyngeal SCC incidence peaked in the 50- to 59-year age group. Detailed geographic distribution analysis of patients at the provincial/territorial, city, and postal code levels identified several patient clusters. Conclusions: This work highlights important epidemiological differences in trends between oral and oropharyngeal cancers, identifies high-incidence postal codes for each malignancy, and correlates incidence/mortality with known risk factors including alcohol/tobacco use and HPV infections, therefore providing a comprehensive understanding of epidemiology for these cancers in Canada.